Optimising sub-metre resolution 3D geomorphic change detection over large areas using multitemporal airborne laser scanning with Sentinel-1 InSAR and Sentinel-2 optical observations - Simon J. Walker; Scott N. Wilkinson; Tim R. McVicar; Pascal Castellazzi; Sana Khan (Remote Sensing of Environment, 2025)

The gender wage gap across life: Effects of genetic predisposition towards higher educational attainment - Alex Bryson; Tim Morris; David Bann; David Wilkinson (Economics & Human Biology, 2025)

Lateralized behaviour in dogs during positive anticipation - Tim Simon; Anna Wilkinson; Elisa Frasnelli; Kun Guo; Daniel S. Mills (Animal Behaviour, 2024)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Blueprints of Effective Biodiversity and Conservation Knowledge Products That Support Marine Policy - Lauren V. Weatherdon; Ward Appeltans; Nadine Bowles-Newark; Thomas M. Brooks; Frances E. Davis; Katherine Despot-Belmonte; Stephen Fletcher; Cristina Garilao; Craig Hilton-Taylor; Tim Hirsch; Diego Juffe-Bignoli; Kristin Kaschner; et al. (Frontiers in Marine Science, 2017)

Persistence and stability of Eastern Afromontane forests: evidence from brevicipitid frogs - Simon P. Loader; F. Sara Ceccarelli; Michele Menegon; Kim M. Howell; Roman Kassahun; Abebe A. Mengistu; Samy A. Saber; Fikirte Gebresenbet; Rafael de Sá; Tim R. B. Davenport; Joanna G. Larson; Hendrik Müller; et al. (Journal of Biogeography, 2014)
Aim The persistence and stability of habitats through time are considered predictors of high levels of biodiversity in some environments. Long‐term habitat persistence and stability may explain the species‐rich, endemic forest fauna and flora of the Eastern Afromontane Biodiversity Region ( EABR ). Using complementary phylogenetic and biogeographical approaches, we examine evolutionary patterns in EABR brevicipitid frogs. Using these data, we test whether brevicipitid history reflects patterns of long‐term forest persistence and/or stability across the EABR . Location East Africa. Methods A dated phylogeny for brevicipitids was constructed using two nuclear and three mitochondrial markers. Alternative diversification models were used to determine signal for constant or varying net diversification rates. Using our dated tree, we identified areas of high phylogenetic diversity ( PD ), and inferred ancestral areas using likelihood and Bayesian approaches. Results Brevicipitids have a long history, with generic diversification among extant lineages pre‐dating the Oligocene (> 33 Ma). Ancestral‐area reconstructions indicate the presence of brevicipitids in the EABR since the Oligocene, and support a scenario of palaeoendemics surviving in EABR refugia. Ancestral‐area reconstructions indicate that the central Eastern Arc Mountains ( EAM ) formed the initial centre of diversification of forest brevicipitids. Measures of PD show that diversity varies across the EABR but is highest in the EAM . Constant net diversification rate in brevicipitids is a significantly better fit than alternative, rate‐variable models. Main conclusions The degree of persistence of forest habitats appears to be a contributing factor to the varying levels of diversity across the EABR in brevicipitids (and other organisms). In contrast to the Southern Highlands and Ethiopian Bale Mountains, the EAM stands out as an area that enabled the constant accumulation of brevicipitid species over a long period of time.

Conflict and Impacts of Divers and Anglers in a Marine Park - Tim P. Lynch; Elizabeth Wilkinson; Louise Melling; Rebecca Hamilton; Anne Macready; Sue Feary (Environmental Management, 2004)

Amphibian Declines and Environmental Change: Use of Remote‐Sensing Data to Identify Environmental Correlates - Cynthia Carey; W. Ronald Heyer; John Wilkinson; Ross A. Alford; J. W. Arntzen; Tim Halliday; Laura Hungerford; Karen R. Lips; Elizabeth M. Middleton; Stan A. Orchard; A. Stanley Rand (Conservation Biology, 2001)
Populations of many amphibian species are declining worldwide, and a few species appear to have become extinct. In an attempt to evaluate the potential usefulness of remote‐sensing techniques as a tool for identifying the causes of these declines, we compiled a database that contains descriptions of 120 localities, both at which declines have been documented and at which no declines are yet known. The number of species involved, dates and degree of declines, habitat characteristics, and other factors are provided for each locality. Four relatively undisturbed areas in northeastern Australia, Costa Rica–Panama, central Colorado, and Puerto Rico were chosen for examination of environmental correlates coincident with mass mortalities at these localities. We used data predicted by models or collected by satellites, airplanes, or direct sampling on the ground to evaluate variations over time in temperature, precipitation, wind direction, UV‐B radiation, and concentrations of certain contaminants at these sites. We asked whether unusual changes in these environmental variables occurred either just in advance of or concurrent with dates of amphibian mass mortalities. The variation in certain environmental variables documented by others (Alexander & Eischeid 2001; Middleton et al. 2001; Stallard 2001 [all this issue]) appears unlikely to have directly caused amphibian deaths. But correlations between these environmental changes and the occurrence of amphibian die‐offs invite further investigation into synergistic interactions among environmental variables and possible indirect causal relationships.